(untitled) (Advances in Civil and Architectural Engineering, 2025)
Woven coir geosynthetics are being investigated as a substitute for geosynthetics in reinforcement applications due to their exceptional technical properties. They are commonly used to strengthen pond ash, which can be substituted for soils that have a low load-bearing capacity. This lowers the overall expense for construction and reduces the demand for natural soil. In this study, three varieties of woven coir geosynthetics, designated as C1, C2, and C3, were used to reinforce pond ash. An experimental test was conducted on a model strip footing lying on pond ash reinforced with coir geosynthetics, focusing on variables such as the number of layers, depth of top reinforcement, and width of reinforcement. In addition, triaxial testing was performed on pond ash reinforced with C2 and C3, including variables such as confining pressure and the number of reinforcing layers. The findings suggest that the inclusion of woven coir geosynthetics significantly enhanced the strength and load-bearing capacity. When a single layer of reinforcement was used with fine pond ash, the performance of the C2 and C3 types of coir geosynthetics varied. However, when several layers of reinforcement were used, the C3 type demonstrated superior outcomes. Increasing the thickness of reinforcement layers and the containing pressure both enhanced the strength of the reinforced pond ash. Multiple regression analyses were performed to develop mathematical models. An analysis revealed a substantial relationship between the measured and predicted levels of ultimate bearing capacity ratio.